Vertical Distribution, Biodiversity, and Some Selective Aspects of the Physicochemical Characteristics of the Larval Habitats of Mosquitoes (Diptera: Culicidae) in Chaharmahal and Bakhtiari Province, Iran - Seyed-Mohammad Omrani; Shahyad Azari-Hamidian (Shahrekord University of Medical Sciences, 2020)
Background and aims: Mosquitoes (Diptera: Culicidae) are still a focus of research because of their role in the transmission of diseases and annoying biting behavior. Source reduction is an effective measure to control mosquito populations, which is based on good knowledge of larval habitats. This study was conducted to obtain that basic knowledge in Chaharmahal and Bakhtiari province. Methods: This study was carried out in 2011 and 2012. Geographical coordinates, altitude, pH, temperature, and the dissolved oxygen level of larval habitats were recorded by relevant devices, followed by documenting physical attributes by direct observation. In addition, the indices of biodiversity were calculated to analyze the vertical biodiversity of species. Finally, the affinity index was calculated to elucidate species co-occurrence. Results: Eighteen species were recovered from 92 larval habitats. Low- (≤ 1400 m), mid- (1401-2000 m), and high- (≥ 2001 m) altitudes lodged 7, 17, and 14 species, respectively. Further, the indices of the species richness and biodiversity for these altitudinal categories were 0.93, 1.94, and 1.58, as well as 1.54, 2.13, and 1.96, respectively. Larval habitats were mostly natural, temporary, with standing but clear water, muddy substrate, sunlit, and with vegetation. Other physicochemical characteristics and affinity of species were described and discussed as well. Conclusion: To the best of our knowledge, this is the first report of vertical distribution and biodiversity of mosquito larvae in Iran. The relative uniformity of physicochemical characteristics of larval habitats was attributed to prevailing water resources in the studied area and sampling design. The oviposition site selection of gravid mosquitoes is still an unresolved problem which needs further investigations.